RIGID PAVEMENT DESIGN NATIONAL ROAD REGION II SOUTH KALIMANTAN PROVINCE SIMPANG HANDIL BAKTI-MARABAHAN ROAD (KM 11+350 - KM 16+350) REGENCY OF BARITO KUALA - Siti Muliani; Yasruddin Yasruddin (CERUCUK, 2017)
Simpang Handil Bakti-Marabahan Road is one of the provincial highways whose traffic activity is quite high. As a road that plays an important role in this road segment is still experiencing transportation problems, namely: increasing the amount of traffic, especially on heavy vehicles that result in easy pavement damage. Therefore, it is necessary to select suitable pavement alternatives for use at this location in accordance with road conditions and the environment. This thesis aims to calculate the pavement thickness and cost draft of Simpang Handil Bakti-Marabahan road.On the roads studied, the road pavement used is a rigid pavement structure (Rigid Pavement) which calculations using the Road Pavement Design Manual No. 4. 02 / M / BM / 2013 which is controlled by the Pd T-14-2003 Method and for the calculation of the cost budget using the Work Unit Price (AHSP) 2013 guideline. The total length of the segment to be used is 5000 m.The results obtained for the road width of 7 m shoulder width 2 x 1.5 m, new pavement includes rigid pavement with 275 mm thick, with LMC thick and Class A Aggregate layer of 150 mm. Budget Costs obtained for Rp. 28.2 million according to the specified unit price.Keywords: Rigid Pavement, Manual Design Method of Pavement Road No. 02 / M / BM / 2013, Method Pd T-14-2003.